Factors associated with ABCDE bundle adherence in critically ill adults requiring mechanical ventilation: An observational design. (October 2020) - DeMellow, Jacqueline M.; Kim, Tae Youn; Romano, Patrick S.; Drake, Christiane; Balas, Michele C.
Abstract: Objective: To identify factors associated with the ABCDEF bundle (A ssess, prevent, and manage pain, B oth, spontaneous awakening and breathing trials, C hoice of sedation/analgesia, D elirium assess, prevent and manage, E arly mobility/exercise and F amily engagement/empowerment) adherence, in critically ill patients during the first 96 hours of mechanical ventilation. Design: Observational study using electronic health record data. Setting: 15 intensive care units located in seven community hospitals in a western United States health system. Patients: 977 adult patients who were on mechanical ventilation for greater than 24 hours and admitted to an intensive care unit over six months. Measurements and main results: Multiple regression analysis was used to examine factors contributing to bundle adherence while adjusting for severity of illness, days on mechanical ventilation, hospital site and time elapsed. ABCDEF bundle adherence was higher in patients on mechanical ventilation for less than 48 hours ( p  = 0.01), who received continuous sedation for less than 24 hours ( p  < 0.001), admitted from skilled nursing facilities ( p  < 0.05), and over the course of the six-month study period ( p  < 0.01). Bundle adherence was significantly lower for Hispanic patients ( p  < 0.01). Conclusions: Our study identified potentially modifiable factors that could improve the team's performance of the ABCDEF bundle in patients requiring mechanical ventilation.